2005
DOI: 10.1007/s11373-005-9019-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen overload by postexercise insulin administration abolished the exercise-induced increase in GLUT4 protein

Abstract: To elucidate the role of muscle glycogen storage on regulation of GLUT4 protein expression and whole-body glucose tolerance, muscle glycogen level was manipulated by exercise and insulin administration. Sixty Sprague-Dawley rats were evenly separated into three groups: control (CON), immediately after exercise (EX0), and 16 h after exercise (EX16). Rats from each group were further divided into two groups: saline- and insulin-injected. The 2-day exercise protocol consisted of 2 bouts of 3-h swimming with 45-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…The increased insulin sensitivity after exercise occurs simultaneously with the accumulation of muscle glycogen stores (Hawley and Lessard, 2008). It is believed that increased muscle glycogen stores after exercise is due to increased GLUT4 (Chou et al, 2005, Tsai et al, 2006 and increased GLUT4 protein displacement from inside the cell to plasma surface (Tsai et al, 2006). The findings of some studies show that exercise (TeixeiraLemos et al, 2011;Eguchi et al, 2013) may impact on AMPK activity and AMPK impact on protein GLUT4 (Teixeira-Lemos et al, 2011;Richter and Hargreaves, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased insulin sensitivity after exercise occurs simultaneously with the accumulation of muscle glycogen stores (Hawley and Lessard, 2008). It is believed that increased muscle glycogen stores after exercise is due to increased GLUT4 (Chou et al, 2005, Tsai et al, 2006 and increased GLUT4 protein displacement from inside the cell to plasma surface (Tsai et al, 2006). The findings of some studies show that exercise (TeixeiraLemos et al, 2011;Eguchi et al, 2013) may impact on AMPK activity and AMPK impact on protein GLUT4 (Teixeira-Lemos et al, 2011;Richter and Hargreaves, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of researches show that stimulating AMPK increase glucose uptake (Hawley and Lessard 2008). It is believed that the increased muscle glycogen stores after the exercise is due to increased GLUT4 (Chou et al, 2005;Tsai et al, 2006)and increased GLUT4 protein translocation from inside the cell to plasma surface (Tsai et al, 2006). The exercise-stimulation increases in the translocation of GLUT4 to the skeletal muscle cell membrane occur in people who are healthy and in patients with T2DM 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased insulin sensitivity after exercise occurs simultaneously with the accumulation of muscle glycogen stores (11). It is believed that increased muscle glycogen stores after exercise is due to increased GLUT4 (12,13) and increased GLUT4 protein displacement from inside the cell to plasma surface (13). The findings of some studies show that exercise (36,37) may impact on AMPK activity and AMPK impact on protein GLUT4 (37).…”
Section: Discussionmentioning
confidence: 99%
“…The increased insulin sensitivity occurs after exercise simultaneously with accumulation of muscle glycogen stores (11). It is believed that the increased muscle glycogen stores after the exercise is due to increased GLUT4 (12,13) and increased GLUT4 protein translocation from inside the cell to plasma surface [13]. In this context, Park et al (2011) reported the increased GLUT4 in skeletal muscle of healthy and diabetic mice after 6 weeks running on a treadmill at a speed of 15 meters per minute (14).…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen-depleting exercise is found to increase expression of the proteins that govern glucose uptake in skeletal muscle, including GLUT4 and mitochondrial enzyme activity [22]. Chou et al [23] therefore studied the effect of exerise and insulin administration on muscle glycogen storage and regulation of GLUT4 protein expression. Exercise induces GLUT4 protein expression and glucose tolerance in rats, but this stimulatory effect is abolished by glycogen overload induced by postexercise insulin administration.…”
Section: Glycogen Overload Downregulates Glut4 Expressionmentioning
confidence: 99%